2018
DOI: 10.1037/dev0000517
|View full text |Cite
|
Sign up to set email alerts
|

Child inhibitory control and maternal acculturation moderate effects of maternal parenting on Chinese American children’s adjustment.

Abstract: The goals of this study were to examine: (a) bidirectional associations between maternal parenting (physical punishment and guilt induction) and Chinese American preschool children's psychosocial adjustment and (b) the role of maternal cultural orientation and child temperament in moderating parenting effects. Participants were Chinese American mothers and children (N = 163, M = 4.56, 53% boys). Mothers reported on their parenting practices at both Wave 1 (W1) and Wave 2 (W2) and their cultural orientations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 84 publications
(157 reference statements)
5
56
1
3
Order By: Relevance
“…The most consistent moderators, then, were maternal age and (particularly) education. The question that remains is whether maternal age and education are associated with slightly reduced stability because of reporting error (e.g., younger and less educated mothers may be less reliable reporters; Roberts, Burchinal, & Durham, ), whether younger and less educated mothers cultivate less optimal child rearing environments (Bradley & Corwyn, ) such as more hostile and punitive parenting (Yu et al ., ), and/or whether their children carry developmental risks that slightly destabilize their temperaments over early childhood (Gilman, Kawachi, Fitzmaurice, & Buka, ; Huaqing Qi & Kaiser, ). Each of these explanations is plausible and supported by the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most consistent moderators, then, were maternal age and (particularly) education. The question that remains is whether maternal age and education are associated with slightly reduced stability because of reporting error (e.g., younger and less educated mothers may be less reliable reporters; Roberts, Burchinal, & Durham, ), whether younger and less educated mothers cultivate less optimal child rearing environments (Bradley & Corwyn, ) such as more hostile and punitive parenting (Yu et al ., ), and/or whether their children carry developmental risks that slightly destabilize their temperaments over early childhood (Gilman, Kawachi, Fitzmaurice, & Buka, ; Huaqing Qi & Kaiser, ). Each of these explanations is plausible and supported by the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This study examined the stability of child temperament by maternal report over a range of 3 years in substantial numbers of girls and boys, firstborns and laterborns, and terms and preterms, comparing mothers of varying ages, educations, anxiety, and depression status, using a standard and well‐established parent report measure. The study of temperament stability enhances understanding of individual differences in childhood and has implications for other areas of development because child temperament has been integrated into models of developing personality, links to children's perceptions and interpretations of their experiences, and shapes the quality of the child–caregiver relationship, processes associated with socialization, and effects of parenting (Bates, ; Bates & Pettit, ; Chen & Schmidt, ; Paulussen‐Hoogeboom, Stams, Hermanns, & Peetsma, ; Porter & Hsu, ; Shiner & Caspi, ; Yu, Cheah, Hart, & Yang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Examination of these two dimensions of psychological control and their specific associations with children's bullying outcomes is warranted therefore. Although research on Western children (Casas et al, 2006;Nelson et al, 2013) show similarly detrimental effects of love withdrawal and guilt induction on child aggression, we expected these dimensions to have differential effects on Chinese children based on our conceptual arguments given previously and emerging empirical evidence for the benign nature of guilt induction among individuals influenced by interdependence-oriented cultures (Rudy et al, 2014;Yu, Cheah, Hart, & Yang, 2018).…”
Section: Psychological Control Dimensions and Child Bullying Aggressionmentioning
confidence: 99%
“…The aforementioned cognitive abilities might serve as moderators between environmental risk and behavioral outcomes: in case of high early life risk, poor cognitive abilities might increase the risk of externalizing behavior problems, while good cognitive abilities could protect against the development of externalizing behavior problems (Masten, 2001). Whereas a number of studies show support for interactions between inhibitory control and parenting as a potential environmental risk factor in the prediction of externalizing behavior problems (Fatima & Sharif, 2017;van Aken et al, 2007;Yu et al, 2018), only one study used a cumulative risk index. Here, it was found that low inhibitory control and low attention both strengthened the positive relation between number of risk factors and a combined score of internalizing and externalizing problems (Lengua, 2002).…”
Section: Inhibitory Control Attention and Vocabulary In Relation Tomentioning
confidence: 99%